Current and emerging therapies for patients with advanced pancreatic ductal adenocarcinoma: a bright future. Issue 3 (March 2020) - Christenson, Eric S; Jaffee, Elizabeth; Azad, Nilofer S
Summary: Pancreatic ductal adenocarcinoma is the seventh leading cause of cancer death worldwide with an estimated 432 242 deaths occurring in 2018. This estimate, in conjunction with the findings that pancreatic ductal adenocarcinoma incidence is rising and that pancreatic ductal adenocarcinoma has the highest case-fatality rate of any solid tumour, highlights the urgency for designing novel therapeutic strategies to combat this deadly disease. Through the efforts of the global research community, our knowledge of the factors that lead to the development of pancreatic ductal adenocarcinoma, its progression, and the interplay between tumour cells and their surrounding microenvironment have improved substantially. Although these scientific advances have not yet translated into targeted or immunotherapy strategies that are effective for most patients with pancreatic ductal adenocarcinoma, important incremental progress has been made particularly for the treatment of specific molecular subgroups of tumours. Although PD-1 inhibitors for mismatch-repair-deficient tumours and NTRK inhibitors for tumours containing NTRK gene fusions are the most recent targeted agents approved by the US Food and Drug Administration, olaparib for germline BRCA -mutated pancreatic ductal adenocarcinoma is expected to be approved soon in the maintenance setting. These recent advances show the accelerated pace at which pancreatic ductal adenocarcinoma drugs are achieving successful clinical outcomes. Here we review the current understanding of the pathophysiology of pancreatic ductal adenocarcinoma, recent advances in the understanding of the stromal microenvironment, current standard-of-care treatment, and novel therapeutic targets and strategies that hold promise for improving patient outcomes. We predict that there will be major breakthroughs in the treatment of pancreatic ductal adenocarcinoma in the next 5–10 years. These breakthroughs will result from the increased understanding of the treatment barriers imposed by the tumour-associated stroma, and from the development of novel approaches to re-engineer the tumour microenvironment in favour of effective anticancer responses.